Infrastructure Quality and Service Performance as Determinants of Truck Rice Distribution Effectiveness: A PLS-SEM Study in Sidenreng Rappang, South Sulawesi - Zulfadly; Hakzah; Hamka Wakkang; Imam Fadly; Muhammad Jabir Muhammadiah (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Food security remains a global strategic concern, yet rice distribution in Indonesia faces persistent inefficiencies. In Sidenreng Rappang—a leading production area of South Sulawesi—59% of truck-based distribution routes are damaged, threatening effectiveness of staple food movement. To examine how infrastructure quality (X1) and supply chain management (X2) affect distribution effectiveness (Y), with service performance (Z) as mediator and inter-agency coordination (M) as moderator. A quantitative explanatory causal design was used with n=200 respondents across 11 active rice milling facilities (purposive stratified sampling; minimum n=155 via the Inverse Square Root Method). Data were collected September–November 2025 using a five-point Likert questionnaire and analyzed through PLS-SEM in SmartPLS 4.1.1.6 with 5,000 bootstrap resamples. Infrastructure Quality was the dominant predictor of Distribution Effectiveness (β = 0.670; t = 12.647; p < 0.001; F² = 1.204). Service Performance significantly influenced Y (β = 0.344; p < 0.001) and acted as a full mediator, transforming SCM and Logistics's negative direct effect (β = −0.145; p = 0.002) into positive indirect contributions (H7: β = 0.144; H8: β = 0.171; p < 0.001). Inter-Agency Coordination was insignificant as direct predictor (β = −0.010; p = 0.397) and moderator across focal paths (H9–H11 rejected). The model showed strong fit (GoF = 0.651; SRMR = 0.081; R² = 0.733). The findings validate the Resource-Based View, positioning road infrastructure as a strategic asset and reinforcing service performance as a critical full-mediating mechanism in staple food distribution. Local authorities should prioritize road rehabilitation and distributor service capacity building.